Hubungan antara Ekspresi Ki-67 dengan Stadium Klinis dan Derajat Histopatologis Karsinoma Sel Skuamosa Serviks - Nita Hertati; Heni Maulani; Zulkarnain Musa; Zen Hafy (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2014)
Background Cervical cancer is the third most common type and the fourth most deadly cancerian women which remains a significant health problem worldwide especially in developing coumtry. Ki-67 is a prototype protein in nuclear which influence cell proliferation rate, hence it can be used as one of parameter to evaluate progressivity of tumor cells in carcinoma cases as the cervical squamous cell carcinoma (SCC). This study aims to determine the relationship between clinical staging of cervical SCC and histopatological grading of the cervical SCC with the expression of Ki-67. Methods This was an observational study with a cross sectional design. Sixty cervical squamousa cell carcinoma archive histopathological slide samples (45 biopsy specimens and 15 radical hysterectomy tissues) were collected for this study from the Anatomical Pathology Department of RSUP dr. Mohammad Hoesin Palembang (January 2008 to July 2013). The samples were stained with Ki-67 antibody and analyzed with respect to patient’s clinical stage and histopatological grade. Results The positivity of Ki-67 expressions were more common in the age of ≤ 50 year-old group, in the non-keratinizing type, in the late clinical staging (stage IIIB) and in the moderatelly differentiated histopathological grade. High scores of the Ki-67 expressions (Ki-67>20%) was predominantly found in the late clinical stage and moderatelly differentiated histopathological grade cases. Statistically, there was a significant relationship (p=0.034) with a strong correlation (r=0.714) between the Ki-67 ecpression and the clinical stage of cervical SCC, but not histopathological grade. Conclusion The higher clinical staging of cervical SCC, the higher expression of Ki-67. Key words: cervical squamous cell carcinoma, clinical staging, histophatological grade, Ki-67.